Research on Digital Transformation and Development of Human Resource Enterprises - Sun, Shougang (Journal of Theory and Practice of Social Science, 2023)
In the process of enterprise development, human resource management has always been an important link of management, it plays a very important role in the future development of enterprises. Under the digital background, strengthening the connection between internal organizations has become an important factor to promote the long-term and stable development of enterprises. Therefore, human resource management has ushered in greater opportunities under this background, but also faces more severe challenges. Digital transformation of human resource management has become an inevitable move for enterprises to maintain strong competitiveness in the fierce competition. Especially at present, the global epidemic has brought impacts to all walks of life, so the organization and management need to adjust according to the enterprise strategy to support the stable development of the business. From the perspective of enterprises themselves, there is an urgent need for enterprises to become stronger, better and bigger. Management needs to further help deepen the reform and promote the quality and efficiency of enterprise operations.